2005
DOI: 10.1007/s00213-004-2131-0
|View full text |Cite
|
Sign up to set email alerts
|

The nature of ecstasy-group related deficits in associative learning

Abstract: Rationale/Objectives: Research has revealed associative learning deficits among users of ecstasy; the present study explored the component processes underlying these deficits. Methods: 35 ecstasy users and 62 non-ecstasy users completed a computerbased, verbal paired-associates learning task. Participants attempted to learn eight sequentially presented word pairs. After all eight had been presented, the first member of each pair was displayed and participants attempted to recall the second. Eight trials were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
42
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 31 publications
10
42
0
Order By: Relevance
“…With regard to information processing speed, the data were originally collected by Wareing (2005); the random letter generation data were originally collected by Wareing et al (2002) and Fisk et al (2004); the reading span. data by Wareing et al (2004); the computation span data by Wareing et al (2004, and Montgomery et al (2005b); the spatial working memory data by Wareing et al (2005); the associative learning data from Montgomery et al (2005a); and the syllogistic reasoning data from Montgomery et al (2005c) and Fisk et al (2005).…”
Section: Methodsmentioning
confidence: 99%
“…With regard to information processing speed, the data were originally collected by Wareing (2005); the random letter generation data were originally collected by Wareing et al (2002) and Fisk et al (2004); the reading span. data by Wareing et al (2004); the computation span data by Wareing et al (2004, and Montgomery et al (2005b); the spatial working memory data by Wareing et al (2005); the associative learning data from Montgomery et al (2005a); and the syllogistic reasoning data from Montgomery et al (2005c) and Fisk et al (2005).…”
Section: Methodsmentioning
confidence: 99%
“…Research from our laboratory has previously demonstrated that ecstasy users are impaired on executive function (spatial working memory- Wareing et al 2004, memory updating-Montgomery et al 2005a, access to semantic memory- Montgomery et al 2005a) and other working memory/executive based tasks (associative learning- Montgomery et al 2005b, syllogistic reasoning-Fisk et al 2005Montgomery et al 2005c). Similar findings have been observed by other authors (see Morgan, 2000, for a review of the literature).…”
Section: Introductionmentioning
confidence: 99%
“…As both executive functioning and working memory underlie associative learning it was suggested that learning processes in MDMA users may also been impaired. Evidence for an ecstasy/polydrug-related deficit in associative learning was observed by Montgomery et al (2005a) and the present paper seeks to further explore this deficit by examining recognition and associative learning in MDMA users.…”
mentioning
confidence: 93%
“…Associative learning refers to a conscious attentional process whereby associations are formed between two previously unrelated stimulus representations (Montgomery et al 2005a). Failure to adequately bind stimuli to form new associations within the context of their occurrence can have obvious implications for the individual.…”
mentioning
confidence: 99%
See 1 more Smart Citation